Association between debulking area of rotational atherectomy and platform revolution speed—Frequency domain optical coherence tomography analysis. Issue 1 (11th April 2019) - Mizutani, Kazuki; Hara, Masahiko; Nakao, Kazuhiro; Yamaguchi, Tomohiro; Okai, Tsukasa; Nomoto, Yohta; Kajio, Keiko; Kaneno, Yasuyuki; Yamazaki, Takanori; Ehara, Shoichi; Kamimori, Kimio; Izumiya, Yasuhiro; et al.
Abstract: Objectives: In this study, we sought to investigate the association between revolution speed of rotational atherectomy (RA) and debulking area assessed by frequency domain‐optical coherence tomography (FD‐OCT). Background: The number of patients with severe calcified coronary artery disease requiring treatment with calcium ablation, such as RA, is increasing. However, there is little evidence available regarding the association between debulking area and revolution speed during RA. Methods: We retrospectively investigated 30 consecutive severely calcified coronary lesions in 29 patients who underwent RA under FD‐OCT guidance. The association between preset revolution speed of RA and burr size‐corrected debulking area of the calcified lesion was evaluated using a multivariable regression model with nonlinear restricted‐cubic‐spline, which can help assess nonlinear associations between variables. Results: The median age of study participants was 73 years (quartile 65–78); 82.8% were male. The median burr size was 1.5 mm (1.5–1.75); median total duration of ablation was 120 s (100–180). FD‐OCT revealed that the post‐procedural minimum lumen area increased significantly from 1.64 mm 2 (1.40–2.09) to 2.45 mm 2 (2.11–2.98) ( p < .001). In addition, the burr size‐corrected debulking area increased significantly as the preset revolution speed decreased ( p = .018), especially when the revolution speed was less than 150, 000 rpm. This result implies that additional lumen gain will be obtained by decreasing rpm when the burr speed is set at <150, 000 rpm. Conclusions: FD‐OCT demonstrated that RA with lower revolution speed, below 150, 000 rpm, has the potential to achieve greater calcium debulking effect in patients with severe calcified coronary lesions.